In Vitro Differentiation of Adipose-Derived Mesenchymal Stem cells into Cardiac Tissue-Linked Progenitor Cell Cluster Using Fibrin Matrix Based Niche - S, Subha; Ramesh, Renu; Jayakumar, K.; Krishnan, Lissy K (Cardiology and Cardiovascular Medicine, 2020)
Human adipose-derived mesenchymal stem cells (hADMSCs) transplantation has been widely explored for restoring post-myocardial infarct heart function, with limited success. Whereas the multipotent nature of hADMSC could benefit regeneration, differentiation into undesired lineages upon transplantation could detriment the effects. Therefore, controlled in vitro lineage commitment of hADMSC into cardiac cells, before transplantation offers a promising strategy towards better tissue regeneration. The function of cardiac tissue may require a coordinated action of mixed cell types such as cardiomyocyte-like cells (CMLs), endothelial-like cells (ELCs), and cardiac fibroblast-like cells (CFLs). Therefore, as a preliminary step for developing autologous cell-based therapy, this study derived CMLs, CFLs, and ELCs from hADMSCs of cardiovascular disease (CVD) patients. Specifically designed fibrin-based niche aided the lineage commitment of hADMSCs into different cardiac cells. At least two specific markers of each cell type, both at mRNA and protein level, are demonstrated. The co-culturing of hypoxia-induced additional ELC with co-developed CML-CFL-ELC resulted in further upregulation of cardiogenic and angiogenic markers at the transcriptional level. The study confirms the advantage of multipotency of hADMSCs from CVD patients and the designed niche conditions for obtaining viable mixed population cardiac progenitors for potential benefits in individualized MI regeneration approaches.